PERLINDUNGAN HUKUM TERHADAP KERAHASIAAN DATA PRIBADI WAJIB PAJAK DAERAH DI BADAN PENDAPATAN DAERAH KOTA SURABAYA: Perlindungan Hukum Kerahasiaan Data Pribadi Pada Wajib Pajak Daerah - Septia, Vima; Supriyo, Agus (Fakultas Hukum Universitas Jambi, 2023)
Based on Article 1 paragraph 1 of the Law of the Republic of Indonesia Number 27 of 2022 concerning Protection of Personal Data personal data refers to individual information that can be identified directly or through a combination with other data, either through electronic or non-electronic systems. Article 1 Letter a Law of the Republic of Indonesia Number 9 of 1994 concerning Amendments to Law Number 6 of 1983 concerning General Provisions and Tax Procedures explains that taxpayers refer to individuals or entities determined by tax laws and regulations and have obligations taxation, including certain tax collectors or withholding. Protection of taxpayer personal data at the Regional Revenue Agency for the City of Surabaya is important to ensure that data processing takes into account the constitutional rights of taxpayers. Law Number 27 of 2022 concerning Protection of Personal Data gives rights to personal data subjects to delay or limit the processing of their personal data. This study uses a normative method to evaluate whether the interpretation of personal data protection in Law Number 27 of 2022 concerning Personal Data Protection has been integrated into the Law of the Republic of Indonesia Number 7 of 2021 concerning Harmonization of Tax Regulations and Law of the Republic of Indonesia Number 6 of 2023 regarding the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation. This study also aims to demonstrate efforts to protect the law regarding the confidentiality of personal data of taxpayers in the Surabaya Regional Revenue Agency. In conclusion, this study provides an overview of the existing legal protections for personal data of taxpayers and evaluates the suitability of data protection regulations with applicable tax regulations.